A regular wide QRS complex tachycardia with fusion beats?. Issue 6 (7th October 2020) - Arias, Miguel A.; Pachón, Marta; Martín‐Sierra, Cristina
Abstract : A case of wide complex tachycardia with isolated QRS complexes of different amplitude suggesting that this was ventricular tachycardia.